Whole genome sequence association analysis of Brain MRI measures. (20th December 2022) - Shade, Lincoln MP; Satizabal, Claudia L; Glahn, David C; Mosley, Thomas H; Heckbert, Susan R.; Launer, Lenore J.; Yanek, Lisa R; Bis, Joshua C; Smith, Jennifer A; DeCarli, Charles S.; Arnett, Donna K; Psaty, Bruce M.; et al.
Abstract: Background: Genome‐wide association studies (GWAS) of brain volumes have identified common genetic variants with modest effect sizes that lie mainly in non‐coding regions. We sought to identify low frequency and rare variants influencing brain volumes by performing association analyses using whole‐genome sequence data from the Trans‐Omics for Precision Medicine (TOPMed) Program. Method: We analyzed up to 7, 607 participants (57% women; 62% European ancestry, 21% African‐Americans, 15% Hispanic/Latino, 2% Chinese‐American), mean age of 60.5 (16.2), from eight TOPMed population‐ or family‐based studies (FHS, GENESTAR, CHS, GENOA, ARIC, CARDIA, MESA, and SAFS). We excluded participants with dementia, stroke, presence of large brain infarcts, tumor or low‐quality scans. We tested the association of hippocampal (HV), total brain (TBV), lateral ventricular (LVV) and intracranial (ICV) volumes to individual genetic variants with minor allele counts ≥ 15 using mixed‐effect linear regression models adjusted for age, age 2, sex, study and the first 10 principal components. Models for HV, TBV and log(LVV) were adjusted for ICV. We accounted for relatedness using an empirical kinship matrix and trait variance variability by using a random effect for study. Result: We detected one novel region with low frequency variants associated with HV (13q14, P = 5.8×10 −9 ). The top 13q14 variant for HV (rs115674829) minor allele frequency (MAF) was 2% in our pooled sample but was more common in the pan‐African 1000 Genomes population (MAF = 14%). This variant lies in LINC00598 at 237kb from FOXO1, a member of the forkhead family of transcription factors that has been linked to Alzheimer's Disease. Additionally, we detected new suggestive associations (P≤10 −7 ) for TBV (16p11) and LVV (1q25, 2q22, 3q13, 5q14, and 10q23), including common variants. Finally, we confirmed the association of common variants in GWAS loci for all traits. Conclusion: Our whole genome sequence analyses revealed intriguing new loci of low‐frequency and common variants, and replicated loci previously associated with brain volumes. Future work will include ancestry‐specific and conditional analyses, as well as gene‐based and scan tests. Supported by: AG058589, AG052409, AG054076, NO1‐HC‐25195, HHSN268201500001I and 75N92019D00031, R01HL131136, P30 AG066546, and K99AG066849.